Faktor-Faktor Yang Mempengaruhi Loyalitas Nasabah Kredit Sepeda Motor - Zulkifli, Irwan (Prisani Cendekia, 2025)
This study aims to analyze the influence of service quality and product quality of BCA's Motorcycle Credit on customer loyalty at BCA KCP Cimanggis. The research employs a quantitative approach with a descriptive method. Data were collected through questionnaires distributed to 75 respondents who are customers of BCA KCP Cimanggis with Motorcycle Credit products. The study utilized the Slovin formula to determine the sample size with a 5% margin of error. Data analysis was conducted using statistical methods, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The findings indicate that both service quality and product quality have a significant and positive impact on customer loyalty. The results provide valuable insights for BCA to enhance its marketing strategies and service improvements to increase customer retention and satisfaction.